Analisis Kepatuhan Peserta Didik Terhadap Tata Tertib Sekolah pada SMP Negeri 2 Barombong Kabupaten Gowa. - Nasrun Hasan; Andi Baso; Siti Aisyah Jamaluddin (JED (Jurnal Etika Demokrasi), 2019)
This study aims to find out: 1) Compliance of students with respect to discipline in the SMP. 2 Barombong, 2) Efforts made by the school to foster student compliance with the discipline in the SMP. 2 Barombong. To achieve these objectives, the researchers used the technique of collecting data through documentation, observation, and interviews. Data that has been obtained from the results of the research are processed 1. Compliance of students with respect to discipline in the Public High School. 2 Barombong 2. Efforts made by the school to foster student adherence to discipline in the SMP. 2 Barombong. This is evidenced by the average student in the SMP. 2 Barombong has obeyed the existing rules so that not many violations occur, while the violations that sometimes arise are only for minor types of violations (not wearing white and white uniforms on Mondays). The factors that form the basis of students' obedience to school discipline are Hedonist, and the type of compliance that belongs to the Hedonist Conformist. 2) Efforts made by schools to foster student compliance with school discipline are divided into 2, namely: 1) Pre-incentive Efforts, which consist of giving / delivering socialization about the importance of student compliance with school discipline, incidental inspection, structuring canteen location. 2) Repressive efforts, which consist of providing strict sanctions against violators, increasing cooperation between BK teachers and homeroom teachers, and supervising individuals (strict supervision / control).Keywords : Analysis, Compliance, School Rules and Students